Era Digitalisasi dan pengaruhnya bagi Perkembangan Pasar Modal Syariah di Indonesia - Uswatun Chasanah; Fatimatus Zahro; Mahfud Ilham Dzikrullah3 (Tasyri` : Jurnal Tarbiyah-Syari`ah-Islamiyah, 2022)
This research aims to analyze the digital era and its influence on the development of the Sharia capital market in Indonesia. The focus of this research is understanding the Sharia capital market, the digital era and how the digital era influences developments in the Sharia capital market in Indonesia. This research is descriptive qualitative type. Collecting primary data from journals, theses, books, etc. The results of this research are that digital has a significant influence on the development of the Sharia capital market in Indonesia. Because transacting via digital can help reduce crime rates, increase the number of people who will invest, speed up the time and distance in transactions, and make it possible to make transactions anytime and anywhere. So with the progress of the digital era, Indonesia's economy will further improve through investment in the capital market.